Total Synthesis of (±)-Dragmacidin E; Problems Solved and Lessons Learned - Feldman, Ken S.; Ngernmeesri, Paiboon (Synlett, 2012)
(±)-Dragmacidin E was synthesized in 25 steps from commercially available 7-(benzyloxy)indole. Key transformations in the preparation of this sponge metabolite include (a) a Witkop cyclization to establish the bridging indole core, (b) cyclo-dehydrative pyrazinone formation to unite the two indole-bearing components, and (c) late-stage guanidine installation through chemoselective carbonyl activation.1 Introduction2 Results and Discussion2.1 Model System Synthesis2.2 (±)-Dragmacidin E Synthesis3 Conclusions
Keywords: total synthesis; alkaloids; marine natural products; Witkop cyclization; pyrazinone